(untitled) (Journal of Economic Research & Business Administration, 2015)
The article examines the export potential of the place and the Republic of Kazakhstan in the international market of flour , as well as the current state of the grain industry . To improve the competitiveness of the country on the basis of the analysis it is determined that it is necessary millers market development as one of the priority sectors of the agro-industrial complex of Kazakhstan .